A novel internal antigen which distinguishes germinal centre cells from other B-cell types. - Pulford, K; Micklem, K; Jones, M; Pezzella, F; Mayne, K; Morrison, H; Thomas, J; Falini, B; Norton, A; Mason, D (1994)
A new monoclonal antibody, 4KB51, is described which labels the majority of B cells in blood and in mantle and marginal zones but not germinal centre lymphocytes or plasma cells. Antibody 4KB51 also stains monocytes, neutrophils and the majority of T cells. It recognizes an intracellular antigen of 160,000 MW (unreduced) and 68,000 MW (reduced). Antibody 4KB51 labels the tumour cells in all cases of hairy cell leukaemia and in four of the 16 cases of centrocytic B-cell lymphoma studied. No labelling of the other lymphomas (114 cases) or lymphoid leukaemias (13 cases) tested was seen. Antibody 4KB51 may be of value in defining B-cell subsets and in the differential diagnosis of hairy cell leukaemia and centrocytic lymphomas. The pattern of reactivity of 4KB51 suggests that its target antigen may play a functional role, possibly involved in lymphocyte homing.